Technological Issues Of Forming Basic Spiritual-Moral Competences In Future Educators - Ismailov Yakubjon Kuchkarboevich (Zien Journals, 2025)
The article analyzes the technological issues of forming basic spiritual and moral qualities in future teachers on a scientific and theoretical basis. The author substantiates the need to modernize the spiritual and moral education of students in connection with the Concept of Continuous Spiritual Education being implemented in Uzbekistan. The article describes the pedagogical conditions that ensure the development of such qualities as loyalty to the Motherland, responsibility, tolerance, ideological immunity, compassion, legal culture, willpower and innovative thinking in the personality of a future teacher. The study shows on a scientific basis that the future teacher is both an object and a subject in the process of education, and that the system of spiritual and moral competencies is a leading factor in preparation for pedagogical activity. The important importance of the spiritual and educational environment, collective relationships, socio-pedagogical technologies and individual development trajectories in higher educational institutions is revealed.
Keywords: future pedagogue; spiritual and moral education; Concept of continuous spiritual education